Pengaruh Substitusi Ampas Minyak Klentik pada Pembuatan Snack Bar Terhadap Daya Terima Konsumen dan Uji Laboratorium Proksimat - Alya Nur Fajrina; Nur Riska; Mariani (Publikasi Indonesia, 2022)
The aims of this research was to analyze the substitution of klentik oil dreg’s on snack bar 40%, 60% and 80% of amount percentage on organoleptic aspect as a taste, aroma, textur, color and density with five aspect of assessment each aspect. This research was conducted at the Pastry & Bakery Laboratory of Culinary Education Department, Faculty of Engineering, Jakarta State of University. The panelists of hedonic test in this research are 30 non-active panelist who were the general public. The result of organoleptic test showed that’s substitution klentik oil dregs with 40% and 60% has the similar result of each aspects. With the results of the consumer acceptance assessment of 40% with the aroma aspect with an average of 2.9, the color aspect with an average of 3.2, the taste aspect with an average of 2.3, the texture aspect with an average of 3.9 and the density 1.9. The results of the substitution assessment are 60% for the aroma aspect with an average of 2.77, the color aspect with an average of 2.77, the taste aspect with an average of 2.60, the texture aspect with an average of 3.23 and the density aspect with an average of 2. 3.72 average. The results of the substitution assessment are 80% of the aroma aspect with an average of 2.60, the color aspect with an average of 2.21, the taste aspect with an average of 2.30, the texture aspect with an average of 3.27 and the density aspect with an average of 3 ,60. The result of hedonic test showed that snack bar with 60% substitution of klentik oil dregs is the most preferred to all organoleptic aspects which is classified as like category. Friedman’s test result declared that substitution of klentik oil dregs on snack bar haven’t an effect significantly different on organoleptict aspects such taste, aroma, density, texture and color (?=0,05). Statiscally substitution of klentik oil dregs on snack bar didn’t show significantly resulton each aspect of organoleptict test that it can developed as a modern and healthy snack